Imunoexpressão de marcadores de linfócitos natural killer (nk), cd16+ e cd56+, em biópsias cutâneas de pacientes com hanseníase - Sá, Kelvia Miranda (2015)
Immune response to M leprae is determinant to leprosy evolution and NK cells are important constituents of the innate immune response and can contribute to the adaptive response activation. The aim of this study was to evaluate the immunoexpression of NK cells markers CD16+ and CD56+ in skin lesions of patients with leprosy, before any treatment. A total of 54 skin biopsies of patients with leprosy were evaluated by immunohistochemistry using rabbit anti-human CD16a (clone SP189) from Spring Bioscience® and mouse anti-human CD56 (clone 123C3) from Dako®, together with Envision Flex kit from Dako®. Nineteen cases were from tuberculoid (TT) clinical form, 14 were borderline (BT, BB, BL) and 20 were lepromatous (LL), while one case was from indeterminate form (I). Among them 31 (57,4%) were from male gender and 30 (55,5%) presented positive baciloscopy. The samples were collected at the “Centro de Dermatologia Dona Libânia” in Fortaleza, Ceará, Brazil, and were analysed at the “Laboratório de Técnicas Cito-histopatológicas Especiais do Departamento de Patologia e Medicina Legal da Universidade Federal do Ceará”. Positive controls for the CD16 and CD56 expression were lung tissue and carcinoid tumor, respectively. Fisher, Chi-square, Kruskal-Wallis and Mann-Whitney tests were used to statistical analysis and a p value of <0.05 was considered significant. Differences were observed when expression of CD16+ cells was compared between tuberculoid and borderlines forms (p=0.0329), as also among gender comparisons (p=0.0129). The CD16+ cells in the three different clinical forms groups were also statistically different achieving a p value of 0.0085, and showing a higher median of expression of CD16+ in the TT group. These data suggests that a protective immune response against M. leprae in leprosy requires a balance between NK cells subgroups (CD16+ and CD56+) and that the tuberculoid form presents higher levels of CD16+ cells expression when compared to borderlines and LL forms. In addition, the study suggests that there are possible hormonal or genetic influences on the distribution of NK cell function markers.